Сучасні виклики викладання археологічних дисциплін у вищій освіті, можливості застосування цифрових технологій - Рац Адальберт; Rácz Béla; Rats Adalbert; Крулько Лариса; Krulko Larisa (Видавництво «Код», 2025)
Резюме. Проведене дослідження підтверджує, що сучасні виклики у викладанні археологічних дисциплін є комплексними та багатофакторними. Вони охоплюють системну фінансову вразливість, соціально-економічні бар’єри, а також когнітивні обмеження традиційних педагогічних методів, які не відображають просторову сутність археологічної науки. На основі аналізу системних викликів та можливостей застосування технологій, пропонуються ключові рекомендації для модернізації викладання археологічних дисциплін у вищій освіті.

Abstract. This article provides a critical analysis of the multifaceted challenges facing the teaching of archaeological disciplines within the system of higher education. These challenges are identified as encompassing systemic financial vulnerability, inherited curricular inertia, and the pedagogical limitations of traditional text-based and two-dimensional teaching methods. The necessity for a radical modernization of the educational process is substantiated through the targeted integration of digital technologies, particularly extended reality and 3D modeling technologies. Drawing upon theories of visual and spatial learning, it is argued that these technologies are capable of providing embodied interaction, which is critically important for the formation of professional competencies, as archaeology is inherently a spatial discipline. Specific attention is given to strategies for overcoming the key implementation barriers, which include the high cost of infrastructure, the necessity for targeted training of teaching staff, and the development of ethical standards for digital data governance. The article proposes institutional recommendations aimed at introducing coordinated, studentcentered, and financially balanced approaches to the digital transformation of archaeological education in Ukraine. The digital principle is that digital technologies, especially XR and 3D modeling, offer a single, theoretically grounded mechanism to overcome these limitations, significantly enhancing students’ spatial competence and providing a more realistic understanding of the archaeological context. Furthermore, digital archaeology serves as a powerful integrative course that combines the humanities with STEM disciplines.
Contemporary challenges in teaching archaeological disciplines in higher education, opportunities for digital technology application
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: археологія; вища освіта; цифрові технології; просторова компетентність; фахові компетентності; студентоцентрований підхід